Method for preparing copper alloy-tungsten copper composite electrical contact through laser additive manufacturing

After preparing the nickel or nickel alloy transition layer on the surface of the copper alloy, the W-Cu composite material is prepared by using laser cladding technology, which solves the problems of high preparation costs and poor material performance in the prior art, and realizes the preparation of high-performance and low-cost copper alloy-tungsten copper composite electrical contacts.

CN119549745AActive Publication Date: 2025-03-04江西国创院新材料有限公司 +1

Patent Information

Application Number
CN202411795845.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing copper alloy-tungsten copper composite electrical contact preparation methods have problems such as high preparation cost, low material density, severe copper volatility, and uneven coating structure, making it difficult to achieve composite electrical contacts with excellent performance and good interface bonding.

Method used

Laser cladding technology is used to prepare nickel or nickel alloy transition layer on the clean copper alloy surface, and then cladding W-Cu is carried out to promote solid solution of W and Cu through nickel, forming an excellent metallurgical combination.

Benefits of technology

It realizes the preparation of copper alloy-tungsten-copper composite electrical contacts with a low-cost and short-process, with a simple process and easy control process, which can be automated production, green and environmentally friendly, and pollution-free. At the same time, the conductive and thermal conductivity of the material is improved, the surface is enhanced, and the surface is anti-arc ablation performance is supported, and laser cladding repair is supported, extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549745A_ABST
    Figure CN119549745A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrical electronics and advanced non-ferrous metal additive manufacturing, and particularly relates to a preparation method of a laser additive manufacturing copper alloy-tungsten copper composite electrical contact, which comprises the following steps of: preparing a nickel or nickel alloy coating on a copper alloy base material by adopting coaxial powder feeding laser cladding to serve as a middle layer, and then preparing a tungsten copper coating by laser cladding to obtain the copper alloy-tungsten copper composite electrical contact. The composite electrical contact is composed of a pure copper or copper alloy base material layer, a pure nickel or nickel alloy coating and a tungsten copper coating in sequence. The electrical contact obtained by the invention has relatively high electrical conductivity and thermal conductivity, and also has good arc ablation resistance; the copper alloy-tungsten copper electrical contact is prepared by adopting the laser cladding technology, so that the production cost can be effectively reduced, the production efficiency is improved, meanwhile, later maintenance and repair are facilitated, and the method is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrical engineering, electronics and advanced nonferrous metal additive manufacturing, and specifically relates to a preparation method of a copper alloy-tungsten-copper composite electrical contact manufactured by laser additive manufacturing. Technical Background

[0002] The electrical contact is responsible for connecting and disconnecting the current and is a key component of high and low voltage electrical appliances. Its reliability, durability and stability directly affect the safety performance and service life of the switch. According to the performance requirements of the electrical contact material, the copper alloy material has the advantages of high electrical conductivity, high thermal conductivity and excellent processing performance, but its mechanical strength, wear resistance and ablation resistance are difficult to meet the performance of the electrical contact material. In recent years, W-Cu has been widely used as an electrical contact material due to its high strength, good wear resistance and strong arc ablation resistance. The traditional preparation methods mainly include: melt infiltration method, liquid phase sintering method, etc. When preparing tungsten-copper composite materials by melt infiltration method, the powder particle size and the addition of inducers during pre-sintering of the skeleton have a great influence on the organization. At the same time, the sintering of the tungsten skeleton is prone to uneven porosity, resulting in the formation of closed pores, making it difficult for copper to penetrate. Finally, the attached unpenetrated copper must be removed by processing, which increases the preparation cost; the material prepared by liquid phase sintering has a relatively low density, and there are characteristics such as large-scale volatilization of copper and high cost. The wear and ablation of electrical contacts mainly occur on the surface of the material. Therefore, the preparation of W-Cu coating on copper alloy through surface modification technology can not only retain the excellent electrical and thermal conductivity of copper alloy, but also improve the surface wear resistance, arc erosion resistance and mechanical properties.

[0003] Laser cladding technology has a controllable high-energy and high-power density heat source, which can enable the material to obtain a rapid solidification layer, which can not only refine the structure but also improve the thermal fatigue resistance of the material surface, and it is easy to operate and the equipment is simple. However, due to the high reflectivity of copper and copper alloys to lasers, a transition layer is usually prepared on the surface of copper and copper alloys, and then laser cladding is performed to prepare the coating material. The patent "A method for manufacturing pure copper / copper-chromium alloy composite contact material" (patent number: CN101834077 A) discloses: using a binder to modulate Cu-Cr into a paste and pre-set a certain thickness of coating on the copper surface, and then laser cladding is performed after drying. However, on the one hand, due to the extremely fast solidification speed of the molten pool, the decomposition or insufficient volatilization of the added binder will cause defects such as holes and cracks between the substrate and the coating, seriously affecting its bonding performance; on the other hand, the continuous input of the laser causes the overall temperature of the material to rise, and the pre-set coating may fall off, greatly affecting the cladding process. The use of spraying technology combined with laser remelting is also one of the methods for modifying the surface of copper and copper alloys. For example, the patent "A heat-dissipating tungsten-copper coating material for electronic packaging and its preparation method" (patent number: CN 107620030 A) discloses: plasma spraying W-Cu composite powder onto the surface of oxygen-free copper and then laser remelting. However, due to the rapid heating and cooling characteristics of laser remelting, cracks and coating peeling are easily caused. At present, the preparation of composite electrical contacts with excellent performance and good interface bonding still faces huge challenges. Summary of the invention

[0004] In view of the shortcomings of the current preparation methods of copper alloy-tungsten copper composite electrical contacts, the present invention provides a preparation method of copper alloy-tungsten copper composite electrical contacts by laser additive manufacturing: a nickel or nickel alloy transition layer is prepared on the surface of a clean copper alloy by laser cladding, and then W-Cu cladding is performed. In addition to the good wear resistance and corrosion resistance of the nickel-based alloy itself and certain toughness and good wetting and lubrication properties, the atomic radius, density and specific heat of copper and nickel are very close, and both copper and nickel have face-centered cubic structures, which can form infinite or limited mutual solubility in both solid and liquid states, which is conducive to forming a good metallurgical bond between the substrate and the coating, and is suitable for laser cladding on the surface of copper and copper alloys. For W-Cu composite materials, nickel can also promote the solid solution of W and Cu.

[0005] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions: Step 1: Clean and degrease the processed surface of the pure copper or copper alloy substrate, sandblast, clean, and air-dry at room temperature; cleaning and degreasing is to use acetone solution ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the material surface, and the sandblasting pressure is 0.6 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes.

[0006] Step 2: Place the substrate processed in step 1 in a forming chamber with an oxygen content of less than 2000 ppm for preheating.

[0007] Step 3: Prepare pure nickel or nickel alloy coating by laser cladding on pure copper or copper alloy substrate. The specific process parameters are: laser power 300-500W, scanning rate 300-600mm / min, spot diameter 1.2mm-3mm, overlap rate 40%-60%.

[0008] Step 4: Using tungsten copper powder as raw material, laser cladding is performed on pure nickel or nickel alloy coating to prepare tungsten copper coating. The specific process parameters are set as follows: laser power 200-1000 W, scanning rate 200-800 mm / min, spot diameter 1.2 mm-3 mm, overlap rate 35%-65%.

[0009] Step 5: Machining and cleaning the copper alloy-tungsten copper composite electrical contact to make it meet the industry use standards.

[0010] Furthermore, in step 1, the copper alloy is selected from: a Cu-Cr alloy, a Cu-Sn alloy or a Cu-Zn alloy, and the mass percentage of copper is not less than 50%.

[0011] Furthermore, in step 2, the forming chamber is inert atmosphere, and the preheating temperature of the substrate is not less than 100°C.

[0012] Furthermore, in step three, the raw material for preparing the nickel alloy coating is selected from: one of Ni-Cr alloy, Ni-Mo alloy or Ni-Cu alloy, and the mass percentage of nickel is not less than 60%.

[0013] Furthermore, in step three, the thickness of the pure nickel or nickel alloy coating is not less than 0.02 mm and does not exceed 20% of the thickness of the substrate.

[0014] Furthermore, in step 4, the composition ratio of the tungsten copper powder is W:Cu with a mass ratio of 95 / 5 to 10 / 90.

[0015] Furthermore, in step 4, the thickness of the tungsten copper coating is not less than 0.2 mm and not more than 50% of the thickness of the substrate.

[0016] The copper alloy-tungsten copper composite electric contact prepared by the method of the invention is composed of a pure copper or copper alloy substrate layer, a pure nickel or nickel alloy coating and a tungsten copper coating in sequence.

[0017] The method of the present invention can realize low-cost and short-process preparation of copper alloy-tungsten copper composite electrical contacts, the process is simple, the process is easy to control, and can realize automated production, green and environmentally friendly, and pollution-free. The specific beneficial effects are as follows: (1) Due to the high reflectivity of copper, the laser absorption performance of tungsten copper powder is better than that of pure copper. Small laser energy input will result in the substrate being unable to form a molten pool or the molten pool being narrow and shallow, making it difficult for tungsten copper to form a good metallurgical bond with the substrate and form an excellent coating; excessive laser energy input will cause a large amount of copper in the powder to volatilize, which will not only affect the stability of the cladding process, but also cause uneven coating structure and defects such as holes and cracks. Before the present invention uses laser cladding to prepare a tungsten copper composite material coating, pure nickel or nickel alloy is used as an intermediate layer. On the one hand, it can effectively reduce the reflection of the copper substrate to the laser. On the other hand, nickel can promote the wetting of tungsten and copper, which can significantly improve the uniformity of the structure of the tungsten copper composite material coating and effectively avoid the generation of holes, cracks, etc.

[0018] (2) The electric contact manufactured by the present invention has a core that retains the excellent electrical and thermal conductivity of copper and copper alloys, and a surface that has the excellent arc erosion resistance of tungsten-copper composite materials. When the electric contact reaches the end of its service life and has defects, it can be directly repaired by laser cladding and reused, which greatly reduces costs and waste of resources.

[0019] (3) The method of the present invention uses metal powder to directly clad the functional layers without the need for a binder. During the rapid solidification and crystallization of the cladding layer, the gas generated by the thermal decomposition of the binder is avoided from being retained in the pores formed in the cladding layer and contaminating the surface of the substrate, thereby improving the quality of the fusion of the substrate and the coating. At the same time, the cost is reduced, the process is simplified, and the production process is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 SEM images of the copper alloy-tungsten-copper composite electrical contact prepared in Example 1: (a) low magnification (b) high magnification; Figure 2 SEM images of the copper alloy-tungsten-copper composite electrical contact prepared in Example 2: (a) low magnification (b) high magnification; Figure 3 SEM image of the copper alloy-tungsten copper composite electrical contact prepared in Comparative Example 1; Figure 4 SEM image of the copper alloy-tungsten-copper composite electrical contact prepared in Comparative Example 2. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0022] Step 1: Use pure copper plate as substrate, clean and degrease the substrate surface, sandblast, clean, and air-dry at room temperature; cleaning and degreasing is to use acetone ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the material surface, and the sandblasting pressure is 0.3 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes; air-dry at room temperature.

[0023] Step 2: Fix the substrate on the heating plate of the forming chamber, fill the forming chamber with argon gas, the oxygen content in the chamber is 2000 ppm, and preheat the substrate to 300°C; Step 3: Using pure nickel powder as raw material, laser cladding nickel coating on the surface of the substrate, the cladding process parameters are set as follows: laser power 300W, scanning rate 350mm / min, spot diameter 1.5mm, overlap rate 60%, nickel coating thickness 0.1mm; Step 4: W-40 wt.% Cu powder is used as raw material to clad the tungsten copper coating on the nickel coating. The cladding process parameters are set as follows: laser power 400W, scanning rate 400mm / min, spot diameter size 1.5mm, overlap rate 65%, and total thickness of the tungsten copper coating 0.4mm; Step 5: Machining and cleaning the copper alloy-tungsten copper electrical contact to make it meet the industry standards. Its performance is shown in the following table, and its microscopic morphology is as follows: Figure 1 .

[0024] Hardness (HV0.5) Electrical conductivity (%IACS) Thermal conductivity (W / (m*K)) 162 58 312 Example

[0025] Step 1: Use pure copper plate as the substrate, clean and degrease the substrate surface, sandblast, clean, and air-dry at room temperature; cleaning and degreasing is to use acetone ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the material surface, and the sandblasting pressure is 0.4 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes; air-dry at room temperature.

[0026] Step 2: Fix the substrate on the heating plate of the forming chamber, fill the forming chamber with argon gas, the oxygen content in the chamber is 200ppm, and preheat the substrate to 400℃.

[0027] Step 3: Using Ni-Cr alloy powder as raw material, a nickel alloy coating is clad on the surface of the substrate. The cladding process parameters are set as follows: laser power 400W, scanning rate 500mm / min, spot diameter 2mm, overlap rate 45%, cladding single layer of nickel, and the total thickness of the nickel coating is 0.15 mm; Step 4: Using W-20 wt.%Cu powder as raw material, cladding the tungsten-copper composite coating on the nickel coating. The cladding process parameters are set as follows: laser power 500W, scanning rate 500mm / min, spot diameter size 2mm, overlap rate 50%, and total thickness of tungsten-copper coating 0.6mm; Step 5: Machining and cleaning the copper alloy-tungsten copper composite electrical contact to make it meet the industry standards. Figure 2 and the table below.

[0028] Hardness (HV0.5) Electrical conductivity (%IACS) Thermal conductivity (W / (m*K)) 218 45 287 Example

[0029] Step 1: The pure copper plate is used as the substrate, and the surface of the substrate is cleaned and degreased, sandblasted, cleaned, and air-dried at room temperature; the cleaning and degreasing is to use acetone ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the surface of the material, and the sandblasting pressure is 0.6 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes; finally, air-dry at room temperature.

[0030] Step 2: Fix the substrate on the heating plate of the forming chamber, fill the forming chamber with argon gas with an oxygen content of 500 ppm, and preheat the substrate to 500°C.

[0031] Step 3: Using nickel powder as raw material, cladding nickel coating on the surface of the substrate, the cladding process parameters are set as follows: laser power 500W, scanning rate 700 mm / min, spot diameter 2 mm, overlap rate 50%, and total thickness of nickel coating 0.5 mm; Step 4: Using W-10 wt.%Cu powder as raw material, clad the tungsten-copper coating on the nickel coating. The cladding process parameters are set as follows: laser power 1000 W, scanning rate 750 mm / min, spot diameter size 3 mm, overlap rate 30%, and total thickness of the tungsten-copper coating 1.5 mm; Step 5: Machining and cleaning the copper alloy-tungsten copper composite electrical contact to make it meet the industry use standards. Its performance is shown in the following table.

[0032] Hardness (HV0.5) Electrical conductivity (%IACS) Thermal conductivity (W / (m*K)) 385 18 141

[0033] Step 1: Use a 5mm thick pure copper plate as the substrate, clean and degrease the substrate surface, sandblast, clean, and air-dry at room temperature; cleaning and degreasing is to use acetone ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the material surface, and the sandblasting pressure is 0.4 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes; finally, air-dry at room temperature.

[0034] Step 2: Fix the substrate on the heating plate of the forming chamber, fill the forming chamber with argon gas, the oxygen content in the chamber is 200ppm, and preheat the substrate to 400℃.

[0035] Step 3: Using W-20 wt.%Cu powder as raw material, cladding the tungsten-copper composite coating on the substrate. The cladding process parameters are set as follows: laser power 500W, scanning rate 500mm / min, spot diameter 2mm, overlap rate 50%, and total thickness of tungsten-copper coating 0.3mm; Step 5: Machining and cleaning the copper alloy-tungsten copper composite electrical contact. Its SEM image and performance are as follows: Figure 3 and the table below.

[0036] Hardness (HV0.5) Electrical conductivity (%IACS) Thermal conductivity (W / (m*K)) 136 13 102 Compared with the embodiment, in Comparative Example 1, a nickel coating is not prepared as a transition layer, and a tungsten-copper composite material coating is directly prepared on a copper alloy substrate using the same parameters. It is found that the bonding quality between the coating and the substrate is poor, and there are a large number of holes, which greatly affects the bonding between the coating and the substrate and reduces the performance of the material.

[0037] Step 1: Use a 2 mm thick pure copper plate as the substrate, clean and degrease the substrate surface, sandblast, clean, and air-dry at room temperature; cleaning and degreasing is to use acetone ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the material surface, and the sandblasting pressure is 0.6 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes; finally, air-dry at room temperature.

[0038] Step 2: Fix the substrate on the heating plate of the forming chamber, fill the forming chamber with argon gas, and preheat the substrate to 500°C with an oxygen content of 50ppm.

[0039] Step 3: Using nickel powder as raw material, cladding nickel coating on the surface of the substrate, the cladding process parameters are set as follows: laser power 500W, scanning rate 700 mm / min, spot diameter 2 mm, overlap rate 50%, and total thickness of nickel coating 0.1 mm; Step 4: Using W-25 wt.%Cu powder as raw material, cladding the tungsten-copper composite coating on the nickel coating. The cladding process parameters are set as follows: laser power 1000 W, scanning rate 750 mm / min, spot diameter size 3 mm, overlap rate 50%, and total thickness of tungsten-copper coating 2 mm; Step 5: Machining and cleaning the copper alloy / tungsten copper electrical contact. Its SEM image and performance are as follows: Figure 4 and the table below.

[0040] Hardness (HV0.5) Electrical conductivity (%IACS) Thermal conductivity (W / (m*K)) 216 9 122 Compared with the embodiment, the thickness of the copper coating in Comparative Example 2 is equivalent to the thickness of the substrate. In the obtained copper alloy-tungsten-copper composite electrical contact, obvious defects appear at the junction of the substrate and the coating, and the tungsten phase and copper phase are unevenly distributed in the coating, which greatly reduces the performance of the material.

[0041] The above describes in detail the preferred implementation of this patent, but this patent is not limited to the above implementation. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of this patent.

Claims

1. A method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing, characterized in that: The following steps are involved: Step 1: Clean and degrease the processed surface of the pure copper or copper alloy substrate, sandblast, clean and air-dry at room temperature; cleaning and degreasing is to use acetone solution ultrasonic cleaning for 5 minutes, and then rinse with deionized water; sandblasting is to use corundum to treat the surface of the material, and the sandblasting pressure is 0.6 MPa; cleaning is to use anhydrous ethanol ultrasonic cleaning for 5 minutes; Step 2: placing the substrate processed in step 1 in a forming chamber with an oxygen content of less than 2000 ppm for preheating; Step 3: Prepare pure nickel or nickel alloy coating by laser cladding on pure copper or copper alloy substrate. The specific process parameters are: laser power 300-500W, scanning rate 300-600mm / min, spot diameter 1.2mm-3mm, overlap rate 40%-60%; Step 4: Using tungsten copper powder as raw material, laser cladding is performed on pure nickel or nickel alloy coating to prepare tungsten copper coating. The specific process parameters are set as follows: laser power 200-1000 W, scanning rate 200-800 mm / min, spot diameter 1.2 mm-3 mm, overlap rate 35%-65%; Step 5: Machining and cleaning the copper alloy-tungsten copper composite electrical contact to make it meet the industry use standards.

2. The method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing according to claim 1, characterized in that: In the step 1, the copper alloy is selected from: a Cu-Cr alloy, a Cu-Sn alloy or a Cu-Zn alloy, and the mass percentage of copper is not less than 50%.

3. The method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing according to claim 1, characterized in that: In the step 2, the forming chamber is in an inert atmosphere, and the preheating temperature of the substrate is not less than 100°C.

4. The method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing according to claim 1, characterized in that: In the step 3, the raw material for preparing the nickel alloy coating is selected from: one of Ni-Cr alloy, Ni-Mo alloy or Ni-Cu alloy, and the mass percentage of nickel is not less than 60%.

5. The method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing according to claim 1, characterized in that: In the step 3, the thickness of the pure nickel or nickel alloy coating is not less than 0.02 mm and does not exceed 20% of the thickness of the substrate.

6. The method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing according to claim 1, characterized in that: In the step 4, the composition ratio of the tungsten copper powder is W:Cu with a mass ratio of 95 / 5 to 10 / 90.

7. The method for preparing a copper alloy-tungsten copper composite electrical contact by laser additive manufacturing according to claim 1, characterized in that: In the step 4, the thickness of the tungsten copper coating is not less than 0.2 mm and not more than 50% of the thickness of the substrate.

8. The copper alloy-tungsten copper composite electrical contact prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It is composed of a pure copper or copper alloy substrate layer, a pure nickel or nickel alloy coating and a tungsten copper coating in sequence.

Citation Information

Patent Citations

  • Method for manufacturing pure copper / copper chromium alloy composite contact material

    CN101834077A

  • Heat dissipation type tungsten and copper coating material for electronic packaging and preparing method thereof

    CN107620030A

  • Method for preparing copper-base tungsten coating through compounded process of laser and thermal spraying

    CN101717910A

  • Synchronous laser cladding method of copper-base-surface composite nickel-base alloy

    CN105506620A

  • Laser 3D printing method for tungsten-copper alloy

    CN106903312A

Cited By

  • Tungsten-copper composite material and preparation method and application thereof

    CN119974684A

  • A tungsten copper composite material, its preparation method and application

    CN119974684B

  • Efficient laser cladding preparation method for nickel-based superalloy on surface of copper alloy

    CN121131784A

  • Laser remelting modification method for copper-chromium contact and copper-chromium contact

    CN122073192A